Using open source & low cost rain gauges to support debris flow real-time monitoring in Lima, Peru - Arestegui, Miguel (2021)
Debris flow, locally known as huaycos, impact the east part of the metropolitan city of Lima, capital of Peru. However, after many extreme events such as the one related to the 2017 “Coastal Niño” or the one in 1987, there is a lack of historical data and sufficiently accurate monitoring systems.